THE INFLUENCE OF THE SHADOW ECONOMY ON THE FORMATION OF TAX GAPS - Родченко, Светлана; Лелюк, Наталья; Высоцкая, Инна (SWorldJournal, 2020)
The paper considers tax gaps arising from shadow economic activity. The level of the shadow economy is analyzed by different methods. The amount of tax losses of the state is calculated based on the level of shadow economic activity. It is proposed to use